Non‐catalytic and heterogeneous acid/base‐catalyzed biodiesel production: Recent and future developments. Issue 3 (25th April 2020) - Tran‐Nguyen, Phuong Lan; Ong, Lu Ki; Go, Alchris Woo; Ju, Yi‐Hsu; Angkawijaya, Artik Elisa
Abstract: Biodiesel production technologies, which are non‐catalytic and those involving the use of heterogeneous catalyst(s), have gained much interest owing to its high biodiesel and pure glycerol throughput. During the past 15 years, many studies were devoted to explore new catalysts as well as improve non‐catalytic technologies with aims to ultimately industrialize such biodiesel production processes. This review elucidates the main process parameters that influences non‐catalytic and heterogeneous‐catalyzed biodiesel production processes. The common parameters among these technologies include the process temperature, alcohol/oil molar ratio, pressure, catalyst loading, and feedstock quality. Optimization of these process parameters is discussed according to the use of conventional method (one factor at a time [OFAAT]) or the use of statistical methods such as response surface methodology (RSM), artificial neural network (ANN), and Taguchi method. In addition, recent development on non‐catalytic process and those involving the use of heterogeneous catalyst(s), such as glycerol‐free processes under supercritical conditions of alkyl donors and strategies to improve properties of heterogeneous catalyst, are also reviewed. Finally, insight based on the published techno‐economical evaluations is also tackled, and future prospects and research directions on these technologies are also discussed.